Investigación sobre la aplicabilidad y desarrollo de sistemas de medición de velocidad en la rueda (2006)
Scania CV AB with their group RESB - Chassis Control Systems is interested in a research and analysis of the potential in the wheel speed signals, and to determine if this kind of information can be used in the development of a passive tyre pressure monitoring system (TPMS). The idea of a passive TPMS, is to use the wheel speed signals, generated by existing sensors, to monitor the pressure of the wheels, and exclude the use of extra sensors for this function. This paper introduces a description of the work that has been done on the measurement and analysis of the wheel speed signals